Kakuriyo : bed & breakfast for spirits. 1 - Yuma, Midori; Yuma, Midori (Shojo beat manga., 2019)
"Aoi Tsubaki inherited her grandfather's ability to see spirits--and his massive debt to them. Now she's been kidnapped and taken to Kakuriyo, the spirit world, to make good on his bill. Her options: marry the head of the inn her grandfather trashed, or get eaten by ayakashi. But Aoi isn't the type to let spirits push her around, and she's determined to redeem her grandfather's IOU on her own terms. Aoi wants to work off her debt to the Tenjin-ya inn, but she only has one day to find a position and none of the managers are willing to hire a human! If she can just get someone to see past her family background, Aoi is certain she can prove her worth!"--Page 4 of cover